Analysis of Factors Influencing Trust and its Impact on Repurchase Intention in C2C E-Commerce in Indonesia - Azizah, Riska Nur; Pramukti, Wahyoe; Utami, Winda Putri (Syntax Corporation, 2024)
The use of the internet has transformed individual shopping behaviors, shifting from traditional shopping patterns or visiting physical stores to shopping through online platforms or e-commerce. This behavioral change has undeniably had a significant impact on the retail industry and consumers at large. With the increasing number of e-commerce users, especially in the C2C (consumer to consumer) sector, market competition is becoming more intense. This study focuses on analyzing certain factors such as website appearance, ease of use, free shipping policy, return policy, POD mode of payment, and security that can influence customer trust and its impact on repurchase intention. Data collection was conducted through the distribution of online questionnaires in the Jabodetabek area to customers who had made online purchases in the last three months, using a purposive sampling method with a total of 228 respondents. The research method analysis used the PLS-SEM method. The results of this study indicate that website appearance, free shipping policy, return policy, and security have a positive and significant effect on trust. Meanwhile, ease of use and POD mode of payment have a positive but not significant effect on trust. Furthermore, trust has a positive and significant impact on repurchase intention. This study plays a role for C2C e-commerce management in increasing consumer trust, especially among the millennial generation, and its impact on repurchase intention.